Tufted angioma in ear auricle: importance of the differential diagnosis - Carla Andréa Avelar Pires; Brena Andrade de Sousa; Gabriela Athayde Amin; Maraya de Jesus Semblano Bittencourt; Mario Fernando Ribeiro de Miranda; Francisca Regina Oliveira Carneiro (Sociedade Brasileira de Dermatologia, 2013)
Tufted angioma is an acquired vascular proliferation with specific histological characteristics. The most common clinical features are erythematous macules. It occurs predominantly in children and young adults, especially in the chest and neck. We report the case of a male patient, 12 years old, with an increased right ear auricle associated with erythematous macules and increased local temperature, referred with a diagnosis of lepromatous leprosy; however, this diagnosis was questioned. Histopathology was consistent with tufted angioma.